Cultural Perspectives on Pain Assessment and Opioid Use: International Neuroscience Nursing Research Symposium Conference Proceedings. Issue 3 (3rd June 2021) - Bautista, Cynthia; Amatangelo, Mary P.; Baby, Priya; Cassier-Woidasky, Anne-Kathrin; Dycus, Kaleigh; Edoh, Esther I.; Green, Theresa; Ilano, Karen Czarina S.; Kemboi, Mary; Littlejohns, Linda; Martinez, Rudolf Cymorr Kirby P.; Mastamet, Gladys; et al.
ABSTRACT: INTRODUCTION: In August of 2020, the 4th International Neuroscience Nursing Research Symposium was held. The purpose of the symposium was to share neuroscience nursing research from around the world. One of the topics thought most notable that stimulated a crucial conversation was how different countries assessed pain and their use of opioids for pain management. BACKGROUND: Neuroscience nurses are global. What is not known is their experience with and what challenges exist with pain management for human beings in their country. Crossing geographic and cultural boundaries, pain affects all human beings. Each culture has unique values and beliefs regarding pain. Patient barriers, pivotal in this article, included poverty, poor health literacy, opioid phobia, and cultural as well as social beliefs. RESULTS: Neuroscience nurses from Australia, Brazil, Germany, Singapore, India, Ghana, Kenya, Philippines, South Africa, and the United States each collaborated to provide a short summary of assessing pain and use of opioids for pain management for the neuroscience patient. CONCLUSION: Neuroscience patients have varying degrees of pain based on many factors. Various countries have religious, spiritual, and cultural traditions that influence the reporting and management of pain. Pain assessment and management can be challenging, especially for the neuroscience nurses around the world.